Economic and financial aspects of social security : an international survey. - Richardson, J. Henry (John Henry), 1890- (University of Toronto Press, 1960)
This important book by an experienced authority on social security discusses a subject of vital interest to governments and peoples everywhere. In all countries social security in still experimental, its principles and menthods are being actively reviewed.